Exhaled breath condensate in acute pulmonary embolism; a porcine study of effect of condensing temperature and feasibility of protein analysis by mass spectrometry. (22nd January 2021) - Gade, Inger Lise; Schultz, Jacob Gammelgaard; Cehofski, Lasse Jørgensen; Kjærgaard, Benedict; Severinsen, Marianne Tang; Rasmussen, Bodil Steen; Vorum, Henrik; Honoré, Bent; Kristensen, Søren Risom
Abstract: The search for diagnostic biomarkers for pulmonary embolism (PE) has mainly been focused on blood samples. Exhaled breath condensate (EBC) is a possible source for biomarkers specific for chronic lung diseases and cancer, yet no previous studies have investigated the potential of EBC for diagnosis of PE. The protein content in the EBC is very low, and efficient condensing of the EBC is important in order to obtain high quality samples for protein analysis. We investigated if advanced proteomic techniques in a porcine model of acute intermediate-high-risk PE was feasible using two different condensing temperatures for EBC collection. Seven pigs were anaesthetized and intubated. EBC was collected one hour after intubation. Two autologous emboli were induced through the right external jugular vein. Two hours after the emboli were administered, EBC was collected again. Condensing temperature was either −21 °C or −80 °C. Nano liquid chromatography-tandem mass spectrometry (nLC-MS/MS) was used to identify and quantify proteins of the EBC. A condensing temperature of −80 °C significantly increased the EBC volume compared with −21 °C (1.78 ± 0.25 ml vs 0.71 ± 0.12 ml) while the protein concentration in the EBC was unaltered. The mean protein concentration in the EBCs was 5.85 ± 0.93 µ g ml −1, unaltered after PE. In total, 254 proteins were identified in the EBCs. Identified proteins included proteins of the cytoplasm, nucleus, plasma membrane and extracellular region. The protein composition did not differ according to condensing temperature. The EBC from pigs with acute intermediate-high-risk PE contained sufficient amounts of protein for analysis by nLC-MS/MS. The proteins were from relevant cellular compartments, indicating that EBC is a possible source for biomarkers for acute PE.